Monochromatic Blue Light Activates Suprachiasmatic Nucleus Neuronal Activity and Promotes Arousal in Mice Under Sevoflurane Anesthesia - Liu, Daiqiang; Li, Jiayan; Wu, Jiayi; Dai, Jiaqi; Chen, Xinfeng; Huang, Yujie; Zhang, Shuang; Tian, Bo; Mei, Wei (Frontiers in Neural Circuits, 2020)
Background Monochromatic blue light (MBL), with a wavelength between 400-490 nm, can regulate non-image-forming functions of light in the central nervous system. The suprachiasmatic nucleus (SCN) in the brain has been shown to be involved in arousal-promoting response to blue light in mice. Animal and human studies showed that the responsiveness of the brain to visual stimuli is partly preserved under general anesthesia. Therefore, the aim of this study was to investigate whether MBL promotes arousal from sevoﬂurane anesthesia via activation of the SCN in mice. Methods The induction and emergence time of sevoflurane anesthesia under MBL (460 nm and 800 lux) exposure were measured. Cortical electroencephalograms (EEGs) were recorded and the burst-suppression ratio (BSR) was calculated under MBL during sevoﬂurane anesthesia. The EEGs and local field potential (LFP) recordings with or without locally electrolytic ablated bilateral SCN were used to further explore the role of SCN in the arousal-promoting effect of MBL under sevoflurane anesthesia. Immunoﬂuorescent staining of c-Fos was conducted to reveal the possible downstream mechanism of SCN activation. Results Unlike the lack of effect on the induction time, MBL shortened the emergence time and the EEG recordings showed cortical arousal during the recovery period. MBL resulted in a significant decrease in BSR and a marked increase in EEG power at all frequency bands except for the spindle band during 2.5% sevoﬂurane anesthesia. MBL exposure under sevoflurane anesthesia enhances the neuronal activity of the SCN. These responses to MBL were abolished in SCN lesioned (SCNx) mice. MBL evoked a high level of c-Fos expression in the prefrontal cortex (PFC) and lateral hypothalamus (LH) compared to polychromatic white light under sevoflurane anesthesia, while it exerted no effect on c-Fos expression in the ventrolateral preoptic area (VLPO) and locus coeruleus (LC) c-Fos expression. Conclusions MBL promotes behavioral and electroencephalographic arousal from sevoﬂurane anesthesia via the activation of the SCN and its associated downstream wake-related nuclei. The clinical implications of this study warrant further study.